2013
DOI: 10.2478/raon-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcome of comprehensive therapy in a case of laryngeal synovial sarcoma

Abstract: BackgroundSynovial sarcoma is common in the extremities. Our search revealed only 17 cases of synovial sarcoma of the larynx in the English-language literature.Case reportWe report an additional case of a 37-year-old man with primary laryngeal synovial sarcoma who underwent positron emission tomography/computed tomography (PET/CT) following the treatment. Although the patient received comprehensive therapy including surgery, radiotherapy, repeated chemotherapies, and targeted therapies, he had an unfavourable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…All our patients underwent surgical resection. Upfront dissection of neck lymph nodes is not recommended, underlining the importance of distinguishing a synovial sarcoma from sarcomatoid carcinoma on a pre-operative biopsy [11]. The role of neoadjuvant chemotherapy remains questionable at present [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All our patients underwent surgical resection. Upfront dissection of neck lymph nodes is not recommended, underlining the importance of distinguishing a synovial sarcoma from sarcomatoid carcinoma on a pre-operative biopsy [11]. The role of neoadjuvant chemotherapy remains questionable at present [13].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding adjuvant therapies, Bilgic et al treated an operated case of laryngeal synovial sarcoma with distant metastases to lung with post-op radiotherapy followed by chemotherapy, which proved to be effective and the metastatic nodules disappeared [10]. Bao et al reported the management of local recurrence and distant metastases of a laryngeal synovial sarcoma case with radiation and chemotherapy; the patient however, succumbed to the disease [11]. Thus, the role of adjuvant chemotherapy and radiotherapy is controversial, but these treatment modalities can be offered to patients with incomplete resection and distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…One case of advanced metastatic disease published in 2013 reported on the use of the immunotherapeutic agents nimotuzumab and cetuximab, both monoclonal antibodies against epidermal growth factor receptor. 25…”
Section: Treatmentmentioning
confidence: 99%
“…Adjuvant chemotherapy was administered to 12 adult patients (13.8%) and had no impact on survival [16]. Only few reports (case reports of adult patients with initially localized as well as initially metastatic SS) exist considering OS [19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%